The Queer Citizen : Political attitudes and voting behavior of gay, lesbian and trans* citizens in Germany - Hunklinger, Michael; Justus Liebig University Giessen (My University, 2022)
This PhD thesis uses original data from the LGBTIQ Election Survey 2017 to examine political attitudes (Gabriel 2009) and formal political participation (Ekman/ Amna 2012) on the individual level (voting) and on the collective level (membership in parties, trade unions and NGOs) of gay, lesbian and trans* citizens in Germany. The PhD thesis bridges the gap between conventional political participation research and queer studies and adds to both strings of research. It shows that the majority of gay, lesbian and trans* voters who participated in the survey supports a progressive agenda and therefore votes for and engages with progressive and left-wing parties, as they tend to be more inclusive towards LGBTIQ. However, there is also a certain segment of gay, lesbian and trans* voters who support conservative and right-wing parties. The most important issues for their voting decision were discrimination and homophobia as well as issues like migration and the environment. With regard to formal political participation on a collective level, gay men are more involved in political parties than lesbian women who are more likely to be organized in NGOs. I discuss my findings in the theoretical context of LGBTIQ citizenship and LGBTIQ visibility. This approach positions LGBTIQ people as citizens in the center of analysis and adds to our understanding of citizenship of minorities in our modern societies.
Keywords: queer; citizenship; lgbtiq; political participation; voting; political attitudes; Germany; ddc:320